Harms and Consequences of Victimization - Langton, Lynn (Journal of contemporary criminal justice, 2025)
To meaningfully measure crime and track increases and decreases in public safety, some criminologists have argued for the need to focus on the harms associated with crime rather than counts of the number of crimes. Although numerous other countries have established crime harm indexes, the United States continues to rely heavily on traditional approaches to enumerating crime and to focus primarily on crimes reported to police. This article sets out to examine the harms and consequences of violence as assessed by the National Crime Victimization Survey (NCVS). We provide a descriptive assessment of the physical and social-emotional harms associated with experiencing a violent victimization and use this incident-level information to create an index that moves from simple enumeration to a fuller accounting of harm. We compare harm levels and trends over time to crime counts and by various crime and victim types. We examine how these harms are associated with help-seeking behavior, including reporting to the police and victim assistance. Our aim is to demonstrate how incident-based information about harms can provide additional information about the magnitude of crime and victim help-seeking behavior.